Anti-adipogenic Effects and Mechanisms of Ginsenoside Rg3 in Pre-adipocytes and Obese Mice - Zhang, Longyun; Zhang, Lijuan; Wang, Xiaoyong; Si, Hongwei (Frontiers in Pharmacology, 2017)
Red or black ginseng has been reported more powerful than white/fresh ginseng in dealing with various diseases/conditions including obesity. The major reason is that heating/steaming, the process of making red or black ginseng, produces large amount of bioactive compounds including ginsenoside Rg3 (Rg3), which are trace in fresh or white ginseng. In the present study, Rg3 was applied both in pre-adipocytes and obese mice to investigate the anti-adipogenic effects and relevant mechanisms. Our results show that Rg3 dose-dependently inhibited cell differentiation both in 3T3-L1 cells (30, 50 and 100 μM) and human primary pre-adipocytes (HPAs) (10, 20 and 30 μM). This inhibitory effect is accompanied by the attenuation of the expressions of adipogenic markers including peroxisome proliferator-activated receptor gamma (PPAR-γ), CCAAT/enhancer binding protein alpha (C/EBP-α), fatty acid synthase (FAS), fatty acid binding protein 4 (FABP4) and perilipin. Although dietary intake of Rg3 (0.1mg Rg3/kg diet, 8 weeks) did not significantly affect body weight gain, fat pads and food intake as well as of PPAR-γ expression in fat tissues, we found that hepatic PPAR-γ and C/EBP-α protein expressions and hepatic glutathione reductase and glutathione S-transferase, two major antioxidants molecules were significantly reduced by Rg3. These results suggest that ginsenoside Rg3 may be a potential agent in reducing/preventing obesity.